2020
DOI: 10.1016/j.jse.2019.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Subacromial space outlet in female patients with multidirectional instability based on hypermobile Ehlers-Danlos syndrome and hypermobility spectrum disorder measured by ultrasound

Abstract: The objective of the study was to compare the acromiohumeral distance (AHD) between patients diagnosed with hypermobility type of the Ehlers-Danlos syndrome (hEDS) or Hypermobility 2 Spectrum Disorder (HSD) and healthy controls by evaluating the relative amount the tendon occupies in the subacromial area. Furthermore, the aim was to evaluate if there was a change in AHD with arm elevation within and between groups. MethodsTwenty-nine female hEDS/HSD patients (age 34 ± 12.9 years) and twenty healthy controls (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…This last study found that hEDS/JHS patients had a larger subacromial space outlet than did the control group. 4) In addition, both groups had increased occupation of the supraspinatus tendon in the subacromial area when the arm was elevated compared to the resting position. The last was an indication that narrowing of the subacromial space occurs with arm elevation regardless of the presence of hEDS/JHS syndrome.…”
Section: Shoulder Instability In Heds/jhs Patientsmentioning
confidence: 94%
See 3 more Smart Citations
“…This last study found that hEDS/JHS patients had a larger subacromial space outlet than did the control group. 4) In addition, both groups had increased occupation of the supraspinatus tendon in the subacromial area when the arm was elevated compared to the resting position. The last was an indication that narrowing of the subacromial space occurs with arm elevation regardless of the presence of hEDS/JHS syndrome.…”
Section: Shoulder Instability In Heds/jhs Patientsmentioning
confidence: 94%
“…Another study evaluated the acromiohumeral distance between 29 female patients diagnosed with hEDS or JHS and 20 healthy controls by evaluating the relative amount the supraspinatus tendon occupies in the subacromial area, using ultrasound. 4) The measurements were performed in 45° and 60° of active arm elevation in the scapular plane. This last study found that hEDS/JHS patients had a larger subacromial space outlet than did the control group.…”
Section: Shoulder Instability In Heds/jhs Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is estimated that EDS occurs, on average, in 1/5,000 births in the world population, where the hypermobile type is most common and 90% are women [8,9]. Among the basic symptoms of EDS are elastic skin, susceptibility to injuries and hypermobility of joints [1,10].…”
Section: Introductionmentioning
confidence: 99%